1997
DOI: 10.2307/2411187
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Phenotypes and the Evolutionary Process: I. Direct and Indirect Genetic Effects of Social Interactions

Abstract: Interacting phenotypes are traits whose expression is affected by interactions with conspecifics. Commonly-studied interacting phenotypes include aggression, courtship, and communication. More extreme examples of interacting phenotypes-traits that exist exclusively as a product of interactions-include social dominance, intraspecific competitive ability, and mating systems. We adopt a quantitative genetic approach to assess genetic influences on interacting phenotypes. We partition genetic and environmental eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
496
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(503 citation statements)
references
References 0 publications
7
496
0
Order By: Relevance
“…The slope b ESD corresponds to a maternaleffect coefficient (Kirkpatrick & Lande 1989) mediating the indirect genetic effect of provisioning on offspring begging, and b EDS corresponds to an offspring-effect coefficient mediating the indirect genetic effect of begging on provisioning. A quantitative genetic model for general social interactions with reciprocal effects has derived a solution for trait expression that is formally equivalent to equations (2.7) and (2.12) (Moore et al 1997). The formal equivalence of proximate equilibria for begging and provisioning (this model) and indirect-genetic-effect models (Moore et al 1997) highlights the importance of time-scale in the interpretation of model parameters and equilibrium points.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The slope b ESD corresponds to a maternaleffect coefficient (Kirkpatrick & Lande 1989) mediating the indirect genetic effect of provisioning on offspring begging, and b EDS corresponds to an offspring-effect coefficient mediating the indirect genetic effect of begging on provisioning. A quantitative genetic model for general social interactions with reciprocal effects has derived a solution for trait expression that is formally equivalent to equations (2.7) and (2.12) (Moore et al 1997). The formal equivalence of proximate equilibria for begging and provisioning (this model) and indirect-genetic-effect models (Moore et al 1997) highlights the importance of time-scale in the interpretation of model parameters and equilibrium points.…”
Section: Discussionmentioning
confidence: 98%
“…A quantitative genetic model for general social interactions with reciprocal effects has derived a solution for trait expression that is formally equivalent to equations (2.7) and (2.12) (Moore et al 1997). The formal equivalence of proximate equilibria for begging and provisioning (this model) and indirect-genetic-effect models (Moore et al 1997) highlights the importance of time-scale in the interpretation of model parameters and equilibrium points. It also suggests that the model presented here may apply to general social interactions with reciprocal effects (if there are analogues to the EDS and ESD mechanisms).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Behavioural ecologists have demonstrated that social behaviours in general tend to be flexible in the sense that focal individuals adjust their behaviour to the behaviour of other individual(s) involved in the interaction (Moore et al 1997). Such behavioural flexibility encompasses the whole field of animal communication (Bradbury & Vehrencamp 1998), as well as maternal hormonal effects on offspring behavioural development (e.g.…”
Section: Applications Of the Behavioural Reaction Norm Approachmentioning
confidence: 99%
“…The social environment created by interactions among individuals also becomes a stage for the evolution of the reaction norm (Moore, Brodie, & Wolf, 1997). There may be social effects on phenotypic evolution whenever interacting phenotypes are present, and the fitness of an individual expressing a certain phenotype will be affected by the phenotypes of the individuals with which it is interacting.…”
Section: Discussionmentioning
confidence: 99%